2010
DOI: 10.1007/s12011-009-8583-7
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Action of Se and Cu on the Growth Metabolism of Escherichia coli by Microcalorimetry

Abstract: The biological effect of Se and Cu²(+) on Escherichia coli (E. coli) growth was studied by using a 3114/3236 TAM Air Isothermal Calorimeter, ampoule method, at 37°C. From the thermogenesis curves, the thermokinetic equations were established under different conditions. The kinetics showed that a low concentration of Se (1-10 μg/mL) promoted the growth of E. coli, and a high concentration of Se (>10 μg/mL) inhibited the growth, but the Cu²(+) was always inhibiting the growth of E. coli. Moreover, there was an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Under conditions of high Cu concentration, intestinal Cu-resistant E. coli were selected, and thus, the resistance of E. coli to Cu increased, resulting in an improvement in the adaptability to high levels of Cu and an increase in the abundance of E. coli. However, some previous studies have indicated that Cu inhibits the growth of E. coli in in vitro culture experiments (Ding et al, 2010;Reyes-Jara et al, 2016). This difference may be explained by the fact that the E. coli strain used for in vitro culturing did not possess a Cu resistance system, while the strains of E. coli in the intestinal tract varied, with some being resistant to Cu.…”
Section: Discussionmentioning
confidence: 97%
“…Under conditions of high Cu concentration, intestinal Cu-resistant E. coli were selected, and thus, the resistance of E. coli to Cu increased, resulting in an improvement in the adaptability to high levels of Cu and an increase in the abundance of E. coli. However, some previous studies have indicated that Cu inhibits the growth of E. coli in in vitro culture experiments (Ding et al, 2010;Reyes-Jara et al, 2016). This difference may be explained by the fact that the E. coli strain used for in vitro culturing did not possess a Cu resistance system, while the strains of E. coli in the intestinal tract varied, with some being resistant to Cu.…”
Section: Discussionmentioning
confidence: 97%
“…Our present study showed that in three +Se groups, the contents of GSH and the activities of GSH-Px, SOD, GR, and CAT were all increased when compared with AFB 1 group, and the MDA content was decreased. It may be associated with increased antioxidative function resulting from an increase in activity of GSH-Px whose center is Se [46]. As previous study revealed, Se can inhibit lipid peroxidation [47].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cell numbers drastically decreased when treated with 50 mM or higher Na 2 SeO 3 [ 28 , 29 ]. This phenomenon could be attributed to the interactions between Se and enzymes [ 30 , 31 ], and Se probably exerts inhibiting effect on the activity of enzymes with the catalysis oxidation reactions of S–H groups to S–S or S–Se–S bonds [ 32 ].…”
Section: Resultsmentioning
confidence: 99%